2017
DOI: 10.1007/s12265-017-9744-2
|View full text |Cite
|
Sign up to set email alerts
|

The Dynamics of Cardiovascular Biomarkers in non-Elite Marathon Runners

Abstract: The number of recreational/non-elite athletes participating in marathons is increasing, but data regarding impact of endurance exercise on cardiovascular health are conflicting. This study evaluated 79 recreational athletes of the 2016 Barcelona Marathon (72% men; mean age 39 ± 6 years; 71% ≥35 years). Blood samples were collected at baseline (24-48 h before the race), immediately after the race (1-2 h after the race), and 48-h post-race. Amino-terminal pro-B type natriuretic peptide (NT-proBNP, a marker of my… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
94
1
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(102 citation statements)
references
References 5 publications
(2 reference statements)
4
94
1
1
Order By: Relevance
“…In this study, there was a consistent inverse relation between cTn levels and race duration in both bivariate and multiple regression models ( Table 2, Supplementary Table 3). Previous studies assessing the relationship between the cTn response and race duration have been conflicting: Some studies found a direct correlation (3,16,17), whereas others found an inverse correlation (4,13) or no correlation (11,12,18). Although race duration is a readily available parameter, the interpretation of this variable is complex.…”
Section: Exercise Intensity and Durationmentioning
confidence: 99%
“…In this study, there was a consistent inverse relation between cTn levels and race duration in both bivariate and multiple regression models ( Table 2, Supplementary Table 3). Previous studies assessing the relationship between the cTn response and race duration have been conflicting: Some studies found a direct correlation (3,16,17), whereas others found an inverse correlation (4,13) or no correlation (11,12,18). Although race duration is a readily available parameter, the interpretation of this variable is complex.…”
Section: Exercise Intensity and Durationmentioning
confidence: 99%
“…Exercise-induced increases in cardiac biomarkers, such as troponin, a marker of cardiomyocyte damage, and B-type natriuretic peptide (BNP), a marker of myocardial stress, are common in athletes after endurance exercise [ 29 ]. Recent studies explored the impact of endurance exercise on novel cardiac biomarkers, such as galectin-3, a marker of myocardial fibrosis, [ 30 ] and soluble suppression of tumorigenicity-2 (sST2), a marker of extracellular matrix remodeling and fibrosis [ 31 ]. Resting levels of galectin-3 were higher in athletes ( n = 21) compared to controls ( n = 21), whereas significant increases were observed following a 30-km run (12.8 ± 3.4 to 19.9 ± 3.9 ng/ml, p < 0.001) [ 30 ].…”
Section: Accelerated Coronary Artery Calcificationmentioning
confidence: 99%
“…Similarly, sST2 concentrations increased following a marathon (34.2 to 54.2 ng/ml, p < 0.001), with 68 of 79 athletes (86%) demonstrating a concentration above the upper reference limit. Complete normalization of sST2 levels occurred within 48 h [ 31 ]. Increases in cardiac biomarkers are modest and transient, but the clinical implications of these elevations are unknown.…”
Section: Accelerated Coronary Artery Calcificationmentioning
confidence: 99%
“…Based on studies with adult participants other individual characteristics, other than age, might influence cardiac biomarkers release. Sex differences in cTn and NT-proBNP are controversial (4,6,10,23,30,36,56,80). Previous exercise experience has been negatively associated with cTn release (10,21,47,76) while training load might be not associated with biomarker appearance (18,21,28,33,68,79).…”
Section: Introductionmentioning
confidence: 99%